The ethical challenges of transhumanism - Cortina, Adela (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
Undoubtedly the 4.0 revolution is already the world in which we live and provides very valuable instruments to build a society that can better serve human beings and care for nature from new possibilities. But in order to undertake this path, it is necessary to opt for an ethic that recognizes that it carries intersubjectivity embedded in it, because it is aware that we are not isolated individuals, but that we become people from the reciprocal recognition as valid interlocutors, as beings endowed with dignity and not a simple price, like those who are meat of the same meat and bone of the same bone. This would be a dialogic ethic of cordial reason.